Anti-heat transfer label - Thian, Hui Ning (2019)
For the past decades, shape memory polymers have been developed extensively and become more significant in the industry today. It is a smart material that encompasses the ability to return from a deformed state to its original state with the help of a trigger. The trigger could be heat, light, magnetic field, chemical and electricity. In this report, heat triggered shape memory polymer would be tested and discussed. The purpose of this study is to create an anti-heat transfer label that can be incorporated in the current void label, to act as a failsafe layer should heat is used to tamper the label.